Charge Transport Kinetics in Fluorine-Doped Tin Oxide/Titanium Dioxide/Cadmium Sulfide/Cadmium Selenide Doped with Copper(II)/Zinc Sulfide Photoanode - Nguyen Van Minh; Nguyen Xuan Vinh; Le Minh Nhan; Bui Van Thang; Deepu Thomas (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Quantum dot-sensitized solar cells face major limitations due to electron recombination, which reduces their overall efficiency. To address this challenge, we investigated copper-doped cadmium selenide as a novel approach to enhance charge transport in multilayer photoanodes. The objective of this study was to evaluate the effect of copper doping concentration on charge transport kinetics in TiO₂@CdS@CdSe:Cu²⁺@ZnS photoanodes. Photoanodes with varying Cu contents (0–0.5 mol) were fabricated using the successive ionic layer adsorption and reaction method, followed by ZnS passivation. Electrochemical impedance spectroscopy and current–voltage characterization were employed to analyze charge transfer resistance, fill factor, power conversion efficiency, open-circuit voltage, and short-circuit current density. The optimized Cu(0.2) sample achieved the highest efficiency of 4.68% with a short-circuit current density of 27.35 mA/cm², attributed to improved charge transport, reduced recombination, and enhanced light absorption. However, excessive doping increased recombination and induced structural degradation. In conclusion, appropriate copper doping significantly improves the performance of QDSSCs, providing insights for designing advanced quantum absorber structures in next-generation solar cell technologies. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).